Role of PIN1 in human pathology: Cellular regulation, pathogenesis and therapeutic implications (Review) - Maggio, Julian (2024)
Peptidyl-prolyl isomerase NIMA-interacting 1 (PIN1) plays a crucial regulatory role in cells, and it is the only enzyme capable of selectively binding to phosphorylated proline-directed serine/threonine (pSer/Thr-Pro) residues in target proteins and catalyzing their isomerization. The change in the conformational status of the protein, transitioning between cis and trans, affects its three-dimensional structure and, therefore, alters its function and stability. In this manner, PIN1 plays a role in the development of several human pathologies by regulating essential proteins. In cancer, the enzymatic activity of PIN1 induces conformational changes in essential proteins, promoting oncogenic processes and fostering aggressive tumor characteristics and resistance to chemotherapies. Moreover, the effects of PIN1 on viral infections are notable, as it interacts with viral proteins, enhancing their replication and infection mechanisms. In addition, PIN1 participates in autoimmune, cardiovascular, metabolic, neurodegenerative diseases and osteoporosis. These diverse functions render PIN1 as an attractive therapeutic target, leading to the development of PIN1 inhibitors. The critical role of PIN1 in human pathology is further underscored by its relevance to various diseases, rendering it a potential nexus for novel interventions in human pathologies.